Health care-associated infections in pre-transplant liver intensive care unit: Perspectives and challenges - Elham A. Hassan; Nahla M. Elsherbiny; Abeer S. Abd El-Rehim; Asmaa M.A. Soliman; Asmaa O. Ahmed (Elsevier, 2018)
Background: Health care-associated infections (HAIs) threaten patient's safety worldwide especially in the intensive care units (ICU). In end-stage liver disease (ESLD), the condition is much more complicated. Data regarding HAIs among ESLD patients is lacking. We aimed to assess the incidence of HAIs, risk factors, causative micro-organisms, antimicrobial susceptibilities and mortality rates among patients with end-stage liver disease (ESLD) admitted to pre-transplant liver intensive care unit (LICU). Method: This prospective observational study included 337 ESLD patients admitted to LICU, Al-Rajhi liver center, Assiut University Hospital, Assiut, Egypt between January 2016 and June 2016 and they were followed up for the development of HAI manifestations. The medical history, physical examination and severity of underlying disease were determined. Clinical samples were taken from patients who developed HAIs for microbiological diagnosis and antimicrobial susceptibility testing. Results: A total of 57 (16.9%) ESLD patients developed HAIs with the incidence density of 26.8 per 1000 patient-days. Blood stream infection was the most common (49.1%). Escherichia coli (21.1%) followed by methicillin-resistant Staphylococcus aureus (MRSA) (15.8%) were the commonest bacteria. Multidrug resistant organisms were reported in 52.6% of the isolates. Fungal causes were 15.8% with Candida species dominance. Sphingomonas paucimobilis and Achromobacter dentrificans were reported for the first time as pathogens for HAIs in LICU. Prolonged hospital stay, intravenous line duration, prolonged use of proton pump inhibitors and paracentesis were predictors for HAIs. No significant difference between ESLD patients with and without HAIs regarding mortality (36.8% vs. 48.6%, P = 0.2). Conclusion: High HAI rate among ESLD patients is a matter of worry. Effective surveillance program, active infection control measures and national antibiotic policies are necessary to reduce the burden of HAIs. Keywords: Nosocomial infection, Antimicrobial susceptibilities, Liver intensive care unit